A STUDY ON MERGERS AND ACQUISITIONS IN TELECOM SECTOR – INDIAN SCENARIO - VIJETHA, Dr. J.; ILLANGI, CHITTI BABU (The journal of contemporary issues in business and government, 2022)
With the population increasing day by day, there seems to be a need for more and more development. As a result, there are more and more companies and businesses coming up lately. Some companies function singularly until its existence, but some companies officially join another company and combine to form a single unit. This single unit formed from two or more different companies then works as another unit. The telecom sector of our country is also increasing day by day. With the increasing population, the demands in the telecom sector have also increased. Earlier there used to one old fashioned phone in one society or colony for use by all but in today’s era, a child even of 10 years of age is given a mobile phone and even the lower or poor class can afford a mobile phone too. Today mobile phones have been a necessity more than a luxury where we can keep in touch with our near ones easily. Mergers and Acquisitions are seen even in this sector of the country.